Effects of sweeteners on host physiology by intestinal mucosal microbiota: Example-addition sweeteners in Qiweibaizhu Powder on intestinal mucosal microbiota of mice with antibiotic-associated diarrhea - Qiao, Bo; Liu, Jing; Xiao, Nenqun; Tan, Zhoujin; Peng, Maijiao (Frontiers in Nutrition, 2022)
In recent years, sweeteners have gained massive popularity under the trend of limiting sugar intake. Our previous study found that Qiweibaizhu Powder (QWBZP) could improve gut microbiota dysbiosis and has good efficacy in treating antibiotic-associated diarrhea (AAD). In this study, we investigated the effects of sucrose, sorbitol, xylitol, and saccharin on the intestinal mucosal microbiota of AAD mice treated with QWBZP. When the AAD model was constructed by being gavaged mixed antibiotic solution, Kunming mice were randomly assigned to seven groups: the control (mn) group, the ADD (mm) group, the QWBZP (mq) group, the saccharin + QWBZP (mc) group, the sucrose + QWBZP (ms) group, the xylito + QWBZP (mx) group, and the sorbitol + QWBZP (msl) group. Subsequently, 16S rRNA gene amplicon sequencing was used to analyze the intestinal mucosal microbiota composition and abundance. The results showed that feces from AAD mice were diluted and wet and improved diarrhea symptoms with QWBZP and sorbitol. In contrast, the addition of sucrose, saccharin, and xylitol delayed the healing of diarrhea. The relative abundance of intestinal mucosal microbiota showed Glutamicibacter, Robinsoniella, and Blautia were characteristic bacteria of the mx group, Candidatus Arthromitus, and Bacteroidales_S24-7_group as the typical bacteria of the mn group, Clostridium_innocuum_group as the distinct bacteria of the mm group. Mycoplasma and Bifidobacterium as the characteristic bacteria of the ms group. Correlation analysis of typical bacterial genera with metabolic functions shows that Blautia negatively correlates with D-Glutamine and D-glutamate metabolism. Bacteroidales_S24-7_group has a significant negative correlation with the Synthesis and degradation of ketone bodies. The study confirmed that sucrose, sorbitol, xylitol, and saccharin might further influence metabolic function by altering the intestinal mucosal microbiota. Compared to the other sweetener, adding sorbitol to QWBZP was the best therapeutic effect for AAD and increased the biosynthesis and degradation activities. It provides the experimental basis for applying artificial sweeteners in traditional Chinese medicine (TCM) as a reference for further rational development and safe use of artificial sweeteners.